Cytotoxic lanostanes from fruits of Garcinia wallichii Choisy (Guttiferae). Issue 23 (1st December 2016) - Hongthong, Sakchai; Meesin, Jatuporn; Pailee, Phanruethai; Soorukram, Darunee; Kongsaeree, Palangpon; Prabpai, Samran; Piyachaturawat, Pawinee; Jariyawat, Surawat; Suksen, Kanoknetr; Jaipetch, Thaworn; Nuntasaen, Narong; Reutrakul, Vichai; et al.
Graphical abstract: Abstract: Five new lanostanes, wallichinanes A–E (1 –5 ) together with a known lanostane derivative6 were isolated from the cytotoxic hexanes extract of fruits of Garcinia wallichii Choisy (Guttiferae). The structures of the isolated compounds were established by analysis of spectroscopic data, X-ray diffraction technique as well as comparison with the literature data. The cytotoxicity of all isolated compounds against a panel of cultured cancer cell lines was evaluated. Compound4 exhibited good cytotoxicity with ED50 values ranging from 3.91 to 7.63 μM.